PENERAPAN METODE JARINGAN SYARAF TIRUAN UNTUK KLASIFIKASI CITRA PADA DAUN - Sehatma Roy Levin Sitorus Pane (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Plants are one of the components needed by humans. The science of studying plants has also experienced rapid progress, as has the system of recognizing and assisting plants which are useful in providing various information. The recognition process can be applied to various parts of the plant, one of which is the introduction of leaf images. The process of recognizing leaf images must go through a long learning process, so an image processing technique is used, namely Artificial Neural Networks (ANN). Identification of leaf types using ANN in this experiment uses 3 types of leaf names such as bougenvillea leaves, Geranium leaves, Magnolia Soulangeana leaves, with 30 samples of leaf images with different leaf shapes for each type. The epoch in this Neural Network reaches a maximum value of 1000 iterations. Before conducting image testing, an image training process is first carried out. After testing 30 leaf image samples, 18 training leaf image samples and 12 leaf test image samples were obtained. From the results of this study has a percentage of 91.66%.